ANALISIS KITAB WADZA`IF AL-MUTA’ALLIM: STUDI RELEVANSI NILAI PENDIDIKAN KARAKTER DENGAN MATERI PENDIDIKAN AGAMA ISLAM - MUCH. MAFTUHUL FAHMI; RAHMATULLAH RAHMATULLAH (STAI Ma'had Aly Al-Hikam Malang, 2022)
Various moral problems, identity crises, and social deviations along with the advancement of Science and Technology have become a challenge for modern educators in Indonesia. This phenomenon encourages researchers to explore the values of character education in the book Wadza`if al-Muta'allim by KH. Zainal Abidin Munawwir. This study also analyzes the relevance of these values to the material of Islamic Religious Education in Indonesia based on Permendikbud no. 37 of 2018. The method used by the researcher is a qualitative research type of library research with a descriptive qualitative approach and using content analysis techniques. Researchers managed to find two research results: first, it was found that there were 3 (three) parts of the values of character education in the book of Wadza`if al-Muta'allim, namely: wadza`if al-muta'allim at-tholab era, adab al- muta'allim ma'a ustadzihi, and wadza`if al-muta'allim wa a'maluhu waqta talaqqi ad-dirasah.